Facile Synthesis of a Stable Dihydroboryl BH2− Anion. Issue 46 (18th October 2018) - Arrowsmith, Merle; Mattock, James D.; Hagspiel, Stephan; Krummenacher, Ivo; Vargas, Alfredo; Braunschweig, Holger
Abstract: While the one‐electron reduction of (CAAC Me )BH2 Br (CAAC Me =1‐(2, 6‐diisopropylphenyl)‐3, 3, 5, 5‐tetramethylpyrrolidin‐2‐ylidene) yields a hydride‐shift isomer of the corresponding tetrahydrodiborane, a further reversible reduction leads to the first stable parent boryl anion, [(CAAC Me )BH2 ] −, which acts as a powerful boron nucleophile. Abstract : The parent trap : Successive reductions of a cyclic (alkyl)(amino)carbene (CAAC)‐supported (bromo)dihydroborane yield a hydride‐shift isomer of the corresponding tetrahydrodiborane and the first stable dihydroboryl anion, which acts as a powerful boron nucleophile.